1999
DOI: 10.1164/ajrccm.160.1.9812035
|View full text |Cite
|
Sign up to set email alerts
|

Protection against Methacholine Bronchoconstriction to Assess Relative Potency of Inhaled β2-Agonist

Abstract: The purposes of this study were to estimate the relative dose potency (RP) of two formulations of salbutamol pressurized metered-dose inhalers (Proventil-HFA and Ventolin-CFC MDIs) to protect against methacholine bronchoconstriction, to validate this method and provide recommendations. The protective effects of 100-, 200-, and 400-micrograms doses of Proventil-HFA were compared with the same doses of Ventolin-CFC in 18 adult asthmatics (mean FEV1, 92% predicted; mean baseline PC20 methacholine, 1.8 mg/ml), in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 11 publications
0
30
0
Order By: Relevance
“…Bel and colleagues 14 showed that salbutamol 200 and 400 mg inhaled through a pMDI were both very efficient in shifting to the right the concentration of histamine or methacholine provoking a fall in FEV 1 of 20% or more (PC 20 ) with a small dose related effect for PC 20 histamine but not for PC 20 methacholine. 14 Inhalation of salbutamol 100-400 mg by MDI produces strong bronchoprotection against methacholine that is, however, weakly proportional to the dose since 80% of protection is already achieved with 100 mg. 15 On the other hand, inhalation of 1600 mg salbutamol dry powder on top of regular treatment with salmeterol (50 mg twice daily) or formoterol (12 mg twice daily) did not increase the bronchoprotection towards methacholine. The inability of a dose of salbutamol similar to the one we used and administered through a dry powder inhaler to further improve the bronchoprotection given by long acting b 2 agonists 16 therefore suggests that, in our study, the ultrasonic nebulisation itself may well reinforce the bronchoprotection obtained with salbutamol.…”
Section: Discussionmentioning
confidence: 92%
“…Bel and colleagues 14 showed that salbutamol 200 and 400 mg inhaled through a pMDI were both very efficient in shifting to the right the concentration of histamine or methacholine provoking a fall in FEV 1 of 20% or more (PC 20 ) with a small dose related effect for PC 20 histamine but not for PC 20 methacholine. 14 Inhalation of salbutamol 100-400 mg by MDI produces strong bronchoprotection against methacholine that is, however, weakly proportional to the dose since 80% of protection is already achieved with 100 mg. 15 On the other hand, inhalation of 1600 mg salbutamol dry powder on top of regular treatment with salmeterol (50 mg twice daily) or formoterol (12 mg twice daily) did not increase the bronchoprotection towards methacholine. The inability of a dose of salbutamol similar to the one we used and administered through a dry powder inhaler to further improve the bronchoprotection given by long acting b 2 agonists 16 therefore suggests that, in our study, the ultrasonic nebulisation itself may well reinforce the bronchoprotection obtained with salbutamol.…”
Section: Discussionmentioning
confidence: 92%
“…For example, crossover studies of salbutamol Turbuhaler1 and pMDI required 23 patients to assess bronchoprotective effects against methacholine [24], whereas direct assessment of bronchodilation required o40 evaluable patients [7]. Methacholine-induced bronchoconstriction is now widely accepted as a method of increasing the sensitivity of the efficacy end-point in assessing inhaled b 2 -agonists, and was recently validated in a bioequivalence study of HFA and CFC pMDIs [25]. This placebo-controlled crossover study required 18 asthmatic patients to compare 100, 200, and 400 mg doses of salbutamol from the two devices and Finney bioassay showed a potency ratio of 1.08, confirmed using the nonlinear Emax model [15,25].…”
Section: Discussionmentioning
confidence: 99%
“…20,[37][38][39] These methods used bioassay study design and statistical methods to estimate differences in potency and are capable of making these estimates with a high degree of precision. A study by Lötvall and colleagues 9 was the first to use statistical bioassay methodology to estimate the relative potency of levalbuterol and racemic albuterol.…”
Section: What Is the Appropriate Methods For Examining Relative Potencmentioning
confidence: 99%